Simulation-based learning and assessment for hospital pharmacy service experience among final year pharmacy students in Malaysia - Nazar, Nor Ilyani; Elnaem, Mohamed Hassan Abdelaziz; Ab Rahman, Norny Syafinaz (International Pharmaceutical Federation (FIP), 2020)
This case study reports on the simulation-based learning initiative to replace experiential learning in an actual hospital pharmacy setting, namely Outpatient and Inpatient Pharmacy Services. The report describes the teaching and learning as well as the assessment components given to the students in a Malaysian setting.